2022
DOI: 10.1371/journal.pone.0270096
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of dysphagia in patients with ischemic stroke: A meta-analysis and systematic review

Abstract: Background Dysphagia is a common yet serious complication in stroke patients. We aimed to conduct a meta-analysis and systematic review to evaluate the risk factors of dysphagia in patients with ischemic stroke, to provide insights to the clinical treatment and nursing care of dysphagia. Methods We searched PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI) and Wanfang Database, China Biomedical Literature Database (CBM) for studies on dysphagia in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 49 publications
(48 reference statements)
5
27
0
1
Order By: Relevance
“…With age, decreased muscle tone in the elderly can lead to decreased chewing and swallowing function, and more prone to dysphagia (83). Several previous studies have also shown that age is significantly associated with dysphagia (84,85). BMI not only partially reflects the nutritional status of patients, but also correlates with dysphagia.…”
Section: Factors Associated With Dysphagia In Parkinson's Diseasementioning
confidence: 99%
“…With age, decreased muscle tone in the elderly can lead to decreased chewing and swallowing function, and more prone to dysphagia (83). Several previous studies have also shown that age is significantly associated with dysphagia (84,85). BMI not only partially reflects the nutritional status of patients, but also correlates with dysphagia.…”
Section: Factors Associated With Dysphagia In Parkinson's Diseasementioning
confidence: 99%
“…16 19 On presentation, a lower level of consciousness, higher stroke severity/deficits, and increased stroke volume elevate the dysphagia risk. 16 19…”
Section: Known Gastrointestinal Complications Secondary To Acute Isch...mentioning
confidence: 99%
“…Los ACV del hemisferio derecho no compensan con deglución espontánea, el riesgo de aspiración es frecuente y 1 de cada 3 pacientes requieren nutrición enteral. En el ACV troncoencefálico existe un alto riesgo de presentar disfagia, razón por la que casi la totalidad de los pacientes requieren nutrición enteral (23)(24)(25).…”
Section: Accidenteunclassified